State-government bailouts in Brazil - Afonso S. Bevilaqua (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
As a result of the consolidation of the democracy after the end of the military regime in the mid-1980s, Brazil has gone through a period of remarkable decentralization both in fiscal and political terms. The move towards decentralized management and control of public finances has been followed by a series of bailouts of state governments by the federal government. The lack of effective control on borrowing, coupled with reputational effects originating from these repeated bailout operations, reduced fiscal discipline and created an explosive accumulation of debts in Brazilian states during the last decade. The main purpose of this paper is to assess the determinants of state debt bailouts in Brazil and their relationship with states' fiscal discipline during the 1990s. After providing a brief overview of intergovernmental fiscal relationships in the Brazilian economy, the paper describes state debt developments from the mid-1980s on, with special emphasis on the 1989, 1993 and 1997 state debt bailouts. Then it discusses the determinants of state debt bailouts in Brazil along the lines of a conceptual framework which recognizes that the essence of the bailout question is the issue of moral hazard and also presents empirical evidence that the occurrence of bailouts is associated with lower fiscal discipline in Brazilian states during the 1990s.
Keywords: 330